Microstructure-Engineered Porous Cementitious Composites with Recycled Tire Particles: Orthogonal Optimization for Artificial Reef Applications - Wei Qiao; Yiran Qin; Wei Liu; Mingsheng Wei; Zhihua Luo; Lei Li; Kun Yang (Journal of Marine Science and Engineering)
Porous artificial reef materials made of cement used in the offshore area can repair and improve the ecological environment and enrich fishery resources. In this study, quartz sand was used as the aggregate, high-alumina cement as the cementing agent, and crushed particles of waste tires as the modifier to prepare porous cement–polymer composites. Through orthogonal tests, the effects of the aggregate particle size, the ratio of aggregate to cement, the rubber particle size, and the rubber ratio on the strength and permeability of the porous cement–polymer composites were studied. The significant degrees of different influencing factors were analyzed, and an appropriate configuration scheme for the porous cement–polymer composites was proposed. The experimental results show that the quantity of rubber particles added and the particle size of the rubber particles have a relatively large impact on the properties of the porous cement–polymer composites. Through response surface tests, the interactive effects of various factors in the porous cement–polymer composites on the compressive strength and permeability of the material were verified. The microstructure of the porous cement–polymer composites was observed by SEM. The differences in the microstructure and internal structure between the specimens with a low rubber content and large rubber particle size and those with a high rubber content and small rubber particle size were analyzed, and the influence mechanism of the differences in the microstructure and internal structure on the strength and permeability was proposed.